Market Acceptance Strategy through Customer Centricity Approach in Electric Truck Product Development with Systematic Method Literature Review - Sekar Widyasari Putri; Dominggo Bayu Baskara; Krisnayanti Aditasari (Jurnal Indonesia Sosial Teknologi, 2024)
Transportation is one of the contributors to CO2 pollutants that cause Greenhouse Gas (GHG) emissions, ultimately impacting global climate change. The creation of electric vehicles is concerned with clean energy and handling global climate change. This aligns with the 17 global goals of the United Nations, which are the world agenda to protect planet Earth and for everyone to live a decent life by 2030. However, creating innovations in production and transforming consumers to switch from fuel vehicles to electric vehicles, especially electric trucks, is equally difficult. In 2022, based on data from Vehicle Type Approval, electric truck sales in Indonesia have the lowest number compared to other types of electric vehicles. This study aims to discover how innovation should be carried out and how consumer desires can be fulfilled from these innovations so that the market easily accepts electric truck products with the hope that interest and sales can increase. This study uses a literature study method that provides an overview of how the customer-centricity approach is applied to support innovation during production. The results of this study provide suggestions in the development of electric trucks that companies should not only focus on technology but also focus on consumer needs to adopt electric truck technology such as cost and economic benefits, charging infrastructure available in various locations, government support and policies, social influence, economic and social factors, promotion policies and regional support.